Remote control of quadrotor teams, using hand gestures - Stoica, Adrian; Salvioli, Federico; Flowers, Caitlin (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
This paper addresses the human-centered control of a team (pack) of quadrotors. The control is remote, over the internet. Using simple telepresence tools (video in Skype, showing remote imagery from a ground camera, and from the quadrotors' own livestreaming cameras) the operator uses a command language, UAVL (standing for Unmanned Aerial Vehicle Language) to control quadrotors' behaviors. Seventeen hand gestures are used to express the commands; these are decoded by processing EMG signals collected with an array of EMG electrodes embedded in a BioSleeve mounted on the forearm. Extending prior work with an Unmanned Ground Vehicle Language (UGVL) used with ground robots, UAVL encodes commands used to control quadrotors, individually, or as a team, in direct teleoperated flight, or in preprogrammed flight patterns triggered by the commands.